eB4CAST Approach Improves Science Communication With Stakeholders in a College-Based Health Program - Olfert, Melissa D.; Barr, Makenzie L.; Hagedorn, Rebecca L.; Wattick, Rachel A.; Zhou, Wenjun; Horacek, Tanya M.; Mathews, Anne E.; Kattelmann, Kendra K.; Kidd, Tandalayo; White, Adrienne A.; Brown, Onikia N.; Morrell, Jesse Stabile; et al. (Frontiers in Public Health, 2020)
Communicating scientific results with community partners is often lacking in intervention programs, thus eB4CAST was developed to facilitate impact sharing. This article investigated using the eB4CAST dissemination tool to communicate impact from a campus-based obesity prevention program. Data from Get Fruved RCT university sites collected at baseline were used to generate eB4CAST reports. Experts (n=13) and RCT sites (n=15) were asked to provide feedback on eB4CAST reports based on appeal, understanding, and clarity. On all Likert items, participants rated above 7 on each (out of 10). Positive responses from open-ended questions included eB4CAST reports being clear, visually appealing, and aid in program understanding. Overall, eB4CAST was successful in relaying data and information for the Get Fruved program, thus a means for science communication that could be used in interventions. Utilizing infographics to report data and information is a feasible way to disseminate and communicate in a cost-effective, timely manner.